Bandgap Engineering of Lead‐Free Double Perovskite Cs2AgBiBr6 through Trivalent Metal Alloying. (12th June 2017) - Du, Ke‐zhao; Meng, Weiwei; Wang, Xiaoming; Yan, Yanfa; Mitzi, David B.
Abstract: The double perovskite family, A2 M I M III X6, is a promising route to overcome the lead toxicity issue confronting the current photovoltaic (PV) standout, CH3 NH3 PbI3 . Given the generally large indirect band gap within most known double perovskites, band‐gap engineering provides an important approach for targeting outstanding PV performance within this family. Using Cs2 AgBiBr6 as host, band‐gap engineering through alloying of In III /Sb III has been demonstrated in the current work. Cs2 Ag(Bi1− x M x )Br6 (M=In, Sb) accommodates up to 75 % In III with increased band gap, and up to 37.5 % Sb III with reduced band gap; that is, enabling ca. 0.41 eV band gap modulation through introduction of the two metals, with smallest value of 1.86 eV for Cs2 Ag(Bi0.625 Sb0.375 )Br6 . Band structure calculations indicate that opposite band gap shift directions associated with Sb/In substitution arise from different atomic configurations for these atoms. Associated photoluminescence and environmental stability of the three‐metal systems are also assessed.